The Belgian MicroArray Prenatal (BEMAPRE) database: A systematic nationwide repository of fetal genomic aberrations. (14th November 2018) - Muys, Joke; Blaumeiser, Bettina; Jacquemyn, Yves; Bandelier, Claude; Brison, Nathalie; Bulk, Saskia; Chiarappa, Patrizia; Courtens, Winnie; De Leener, Anne; De Rademaeker, Marjan; Désir, Julie; Destrée, Anne; et al.
Abstract: Objective: With the replacement of karyotyping by chromosomal microarray (CMA) in invasive prenatal diagnosis, new challenges have arisen. By building a national database, we standardize the classification and reporting of prenatally detected copy number variants (CNVs) across Belgian genetic centers. This database, which will link genetic and ultrasound findings with postnatal development, forms a unique resource to investigate the pathogenicity of variants of uncertain significance and to refine the phenotypic spectrum of pathogenic and susceptibility CNVs. Methods: The Belgian MicroArray Prenatal (BEMAPRE) consortium is a collaboration of all genetic centers in Belgium. We collected data from all invasive prenatal procedures performed between May 2013 and July 2016. Results: In this three‐year period, 13 266 prenatal CMAs were performed. By national agreement, a limited number of susceptibility CNVs and no variants of uncertain significance were reported. Added values for using CMA versus conventional karyotyping were 1.8% in the general invasive population and 2.7% in cases with an ultrasound anomaly. Of the reported CNVs, 31.5% would have remained undetected with non‐invasive prenatal test as the first‐tier test. Conclusion: The establishment of a national database for prenatal CNV data allows for a uniform reporting policy and the investigation of the prenatal and postnatal genotype–phenotype correlation. Abstract : What's already known about this topic? In 5%‐10% of pregnancies with a fetal structural anomaly and in 0.5%‐2% of pregnancies without ultrasound anomalies, CMA reveals cryptic, clinically relevant CNVs. What does this study add? This manuscript describes the establishment of a national database for prenatal microarray results in Belgium. This database, which is one of the largest currently available, allows: calculation of added values of microarray over karyotyping for different categories of indications; determination of the most common syndromes, incidental findings, and susceptibility CNVs in the Belgian prenatal population; evaluation of our national reporting policy; and reflection on the effect of the implementation of NIPT.